Racial Microaggressions and Ontological Security: Exploring the Narratives of Young Adult Migrants in Glasgow, UK - Marcus Nicolson (Social Inclusion, 2023)
This study investigates the lived experiences of racial microaggressions faced by young adult migrants in everyday life in Glasgow, UK. The personal stories reported in this study are a direct challenge to the dominant political narrative that Scotland does not have a racism problem. When faced with this discord between narrative and reality, young adultmigrants in Scotland must negotiate both their own lived experiences and biographical narratives to achieve a sense of security. A narrative enquiry methodology is used to explore mundane and everyday interactions for four young adult migrants who have settled in Glasgow over the last 10 years. These accounts of daily life offer a unique view into the everyday racism and racialmicroaggressions faced by this group. Additionally, the opinions of selected Scottish politicians have been collected to gather an additional viewpoint on racism in Scotland. A theoretical perspective stemming from ontological security theory contributes to the racial microaggressions literature in unpacking how individual migrants negotiate traumatic experiences of racism and manage their identities. The analysis explores how migrant individuals may employ coping mechanisms and adopt distinct behaviours to minimise the daily trauma of racism and microaggressions experienced in Scotland. This study, therefore, highlights the potential for interdisciplinary research on racism, narrative, and security studies, and the opportunities for bringing together these distinct perspectives.